The assessment tool: a method to support asynchronous communication between computer experts and laypersons. - Nückles, Matthias; Stürz, Alexander (Computers in Human Behavior, 2006)
Help-desks for hardware and software are a prominent example of Internet-based consulting services. If computer experts' counseling of laypersons is to be effective, the experts need to be able to adjust their way of communicating to fit the knowledge of the layperson. In asynchronous Internet-based communication, the evaluation of an interlocutor's knowledge is more difficult than in face-to-face communication because fewer channels of communication are available. Therefore, an assessment tool has been developed which supports computer experts in evaluating the knowledge of a client who initiates a support inquiry. A dialogue experiment was conducted, which showed that the assessment tool increased the efficiency and effectiveness of computer experts' communication with clients. The assessment tool evidently facilitated the construction of a mental model of the client's knowledge and thereby supported adaptation to the client's communicational needs. Copyright (c) 2006 Elsevier Ltd